2007
DOI: 10.1158/0008-5472.can-06-3927
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated CDC25A Expression Promotes Mammary Tumorigenesis with Genomic Instability

Abstract: Checkpoint pathways help cells maintain genomic integrity, delaying cell cycle progression in response to various risks of fidelity, such as genotoxic stresses, compromised DNA replication, and impaired spindle control. Cancer cells frequently exhibit genomic instability, and recent studies showed that checkpoint pathways are likely to serve as a tumor-suppressive barrier in vivo. The cell cycle-promoting phosphatase CDC25A is an activator of cyclin-dependent kinases and one of the downstream targets for the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…CDC25A is overexpressed in a number of tumors, and mouse models indicate a rate-limiting role for CDC25A in tumorigenesis. 41,42 Thus, it could be interesting to investigate if there is an inverse correlation between CDC25A and NEK11 in primary tumors.…”
Section: Role Of Nek11 In the Absence Of Dna Damagementioning
confidence: 99%
“…CDC25A is overexpressed in a number of tumors, and mouse models indicate a rate-limiting role for CDC25A in tumorigenesis. 41,42 Thus, it could be interesting to investigate if there is an inverse correlation between CDC25A and NEK11 in primary tumors.…”
Section: Role Of Nek11 In the Absence Of Dna Damagementioning
confidence: 99%
“…3,4 Further, hemizygous disruption of CDC25A inhibits cellular transformation and mammary tumorigenesis in mice, suggesting that a low level of CDC25A protein plays a rate-limiting role in transformation and tumor initiation mediated by oncogene such as H-ras 12 and neu. 5,6 Finally, overexpression of CDC25A and CDC25B proteins has been observed in a wide variety of human tumors (see ref. 2 and 7 for review), and these observations have often been linked to a poor prognosis, suggesting an important role in tumor behavior.…”
mentioning
confidence: 99%
“…25 In another recent study using MMTV-CDC25A transgenic mice we demonstrated that CDC25A overexpression in the mouse mammary gland is insufficient to cause spontaneous tumors but does cooperate with neu or ras oncogene. 37 The MMTV-CDC25A transgene significantly accelerates MMTV-ras or -neu-induced mammary tumorigenesis, in association with mis-coordinated cell cycle progression with enhanced genomic instability. Furthermore, Cdc25A heterozygous (+/-) knockout mice are significantly resistant to MMTV-neu or -ras induced oncogenesis.…”
mentioning
confidence: 99%